CONSULTANCY VERSUS ENTREPRENEURIAL BEHAVIOUR IN RURAL AREAS - Anna Parzonko (Acta Scientiarum Polonorum. Oeconomia, 2010)
There are many factors that support undertaking entrepreneurial actions, for example the activity of various institutions and organizations in rural areas. In the article there has been presented the activity of agronomical advisory centres focusing especially on its educational and dissemination aspect. An attempt has been made to answer a question, how does the activity of the institutions affect shaping the entrepreneurial attitudes of village residents.